Development of a CBT Application Using a Prototype Method for Major Determination Based on Talents and Interests - Musdalipa Mahyeandra; Ika Parma Dewi; Rizkayeni Marta; Lativa Mursyida; Hafizul Fahri Hanafi (Ali Institute of Reseach and Publication, 2025)
Computer-Based Test (CBT) is a computer-based examination system used as a medium for administering tests. The presentation and selection of questions are computerized so that each participant receives a different set of questions. This system is developed to minimize cheating, question leaks, limited number of questions, and damage to questions, as well as to ensure more accurate exam results. The problem faced in this study is the inaccuracy in determining the majors for several new students at SMKN 1 Sitiung. This study aims to develop a CBT application that can help determine the majors of new students based on their talents and interests. The research method used is the prototype method, which includes three stages: Listening to the Customer, Building or Revising the Mock-up, and Testing. The results of the study show that the developed CBT application is able to help schools determine student majors more accurately, minimize errors in major placement, and ensure that students are placed according to their talents and interests.